Coming Full Circle: How Health Worker Motivation and Performance in Results-Based Financing Arrangements Hinges on Strong and Adaptive Health Systems - Sumit Kane; Crecentia Gandidzanwa; Ronald Mutasa; Irene Moyo; Chenjerai Sismayi; Patron Mafaune; Marjolein Dieleman (Kerman University of Medical Sciences, 2019)
Background This paper presents findings from a study which sought to understand why health workers working under the results-based financing (RBF) arrangements in Zimbabwe reported being satisfied with the improvements in working conditions and compensation, but paradoxically reported lower motivation levels compared to those not working under RBF arrangements. Methods A qualitative study was conducted amongst health workers and managers working in health facilities that were implementing the RBF arrangements and those that were not. Through purposeful sampling, four facilities in RBF implementing districts that reported poor motivation and satisfaction, were included as study sites. Four facilities located in non-RBF districts which reported high motivation and satisfaction were also included. Data was collected through in-depth interviews and analyzed using the framework approach. Results Results based financing arrangements introduce a wide range of new institutional arrangements, roles, tasks, and ways of doing things, for facility staff, facility managers and, district and provincial health management teams. Findings reveal that insufficient preparedness of people and processes for this change, constrained managers and workers performance. Results based financing arrangements introduce explicit and tacit changes, including but not limited to, incentive logics, in the system. Findings show that unless systematic efforts are made to enable the absorption of these changes in the system: eg, through reconfiguring the decision space available at various levels, through clarification of accountability relationships, through building personnel and process capacities, before instituting changes, the full potential of the RBF arrangements cannot be realised. Conclusion Our study demonstrates the importance of analysing existing institutional, management and governance arrangements and capabilities and taking these into account when designing and implementing RBF interventions. Introducing RBF arrangements cannot alone overcome chronic systemic weaknesses. For a system wide change, as RBF arguably is, to be effected, explicit organisational change management processes need to be put in place, across the system. Carefully designed processes, which take into account the interest and willingness of various actors to change, and which are cognizant of and constructively engage with potential bottlenecks and points of resistance, should accompany any health system change initiative.